Co-processing potential of HTL bio-crude at petroleum refineries – Part 1: Fractional distillation and characterization. (1st February 2016) - Hoffmann, Jessica; Jensen, Claus Uhrenholt; Rosendahl, Lasse A.
Abstract: This study presents detailed chemical and thermophysical analysis of bio-crude from a continuous hydrothermal liquefaction research plant. Current research on bio-crude focuses mainly on specific biomass feedstocks and conversion process conditions and resulting yields rather than on bio-crude properties for downstream processing. This study contributes to the next level of research, where HTL bio-crude is evaluated as a potential refinery co-processing feedstock with regard to bulk and fractional properties. The bio-crude used in the current work has been produced from a hardwood feedstock. Bio-crude assays, adapted from conventional crude oil assays, have been obtained, including fractionation of the bio-crude through 15:5 vacuum distillation. The bio-crude and its fractions have been analyzed with respect to heating value, elemental composition, density and oxygen-containing functional groups. Results show a highly promising bio-crude quality, with a higher heating value of 40.4 MJ/kg, elemental oxygen content of 5.3 wt.%, a specific gravity of 0.97 and a distillation recovery of ∼53.4 wt.% at an atmospheric equivalent temperature (AET) of 375 °C, . Results show that only minor upgrading is needed to achieve co-processing properties and to obtain a refinery bio-feed. This forms the basis for subsequent assessment of drop-in and co-processing potential and parametric upgrading trials of the bio-crude presented in part 2 of this work.